Investigating vegetation–climate feedbacks during the early Eocene - C. A. Loptson; D. J. Lunt; J. E. Francis (Climate of the Past, 2014)
Evidence suggests that the early Eocene was a time of extreme global warmth. However, there are discrepancies between the results of many previous modelling studies and the proxy data at high latitudes, with models struggling to simulate the shallow temperature gradients of this time period to the same extent as the proxies indicate. Vegetation–climate feedbacks play an important role in the present day, but are often neglected in these palaeoclimate modelling studies, and this may be a contributing factor to resolving the model–data discrepancy. Here we investigate these vegetation–climate feedbacks by carrying out simulations of the early Eocene climate at 2 × and 4 × pre-industrial atmospheric CO 2 with fixed vegetation (homogeneous shrubs everywhere) and dynamic vegetation. The results show that the simulations with dynamic vegetation are warmer in the global annual mean than the simulations with fixed shrubs by 0.9 °C at 2 × and 1.8 °C at 4 ×. Consequently, the warming when CO 2 is doubled from 2 × to 4 × is 1 °C higher (in the global annual mean) with dynamic vegetation than with fixed shrubs. This corresponds to an increase in climate sensitivity of 26%. This difference in warming is enhanced at high latitudes, with temperatures increasing by over 50% in some regions of Antarctica. In the Arctic, ice–albedo feedbacks are responsible for the majority of this warming. On a global scale, energy balance analysis shows that the enhanced warming with dynamic vegetation is mainly associated with an increase in atmospheric water vapour but changes in clouds also contribute to the temperature increase. It is likely that changes in surface albedo due to changes in vegetation cover resulted in an initial warming which triggered these water vapour feedbacks. In conclusion, dynamic vegetation goes some way to resolving the discrepancy, but our modelled temperatures cannot reach the same warmth as the data suggest in the Arctic. This suggests that there are additional mechanisms, not included in this modelling ...